PENGARUH OBEDIENCE PRESSURE, KOMPLEKSITAS TUGAS DAN SENIORITAS AUDITOR TERHADAP AUDIT JUDGMENT - Tanoto, Ruliff; Suputra, I.D.G. Dharma (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The purpose of this study was to examine the influence of obedience pressure, complexity task and seniority auditor on audit judgment. Research conducted in the public accounting firm registered with the Indonesian Institute of Accountants (Certified) region of Bali in 2016. The sampling technique using saturated or census sampling. The data collection is done by distributing questionnaires to auditors. Independent auditor in carrying out audit tasks required an audit or audit policy judgment. The number of respondents are 50 auditors by using census method with technique analysis use multiple regression in this research. The results of this analysis showed that obedience pressure and complexity task have effect on audit judgment. Likewise, seniority auditor have effect on audit judgment.
Keywords: Obedience Pressure, Complexity Task, Seniority Auditor, Audit Judgment